2019
DOI: 10.22452/mjlis.vol24no1.4
|View full text |Cite
|
Sign up to set email alerts
|

The structure and evolution of scientific collaboration from the perspective of symbiosis

Abstract: This paper introduces a novel quantitative metric called the Symbiosis Degree Index for measuring the degree of symbiosis between subjects, which we apply it to analyzing scientific collaboration patterns between researchers. We study the network characteristics of scientific collaboration based on the resultant published research papers indexed in the Web of Science, considering the role of symbiosis. Analyses through our symbiosis metric of the relationship between a pair of mentor and mentee show substantiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The distinction between strong and weak ties has been a subject of research. Liu et al (2019) observed several nodes with high connection strength in the collaboration network. This phenomenon has become one of the non-trivial attributes of scientific collaboration.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The distinction between strong and weak ties has been a subject of research. Liu et al (2019) observed several nodes with high connection strength in the collaboration network. This phenomenon has become one of the non-trivial attributes of scientific collaboration.…”
Section: Introductionmentioning
confidence: 96%
“…Apart from weak and strong ties, superpartners with high collaboration intensity usually emerge. It has been shown that super-partnership exerts higher impacts on academic performance than its counterparts (Liu et al, 2019). Petersen (2015) quantified the impact of super-partners and found that they helped to produce above-average research output and increased the citation frequency of each paper by 17% (Petersen, 2015).…”
Section: Introductionmentioning
confidence: 99%